The effects of blood flow restriction combined with resistance training on post-activation potentiation: A meta-analysis - Zhao, C.; Su, R.; Wu, J.; Kang, X.; Li, J.; Zhang, Z. (Science & Sports, 2025)
Background and objective Post-activation potentiation (PAP) refers to the improvement of explosive power in a short period of time, but it needs to be induced by high-intensity resistance training. It has been reported that blood flow restriction combined with low-intensity resistance training (BFR-RT) can produce similar effects on skeletal muscle as high-intensity resistance training. However, the number of studies on the induction of PAP by BFR-RT is limited. Therefore, this study explored the effect of BFR-RT on PAP by pooling relevant studies.